2000
DOI: 10.1128/aem.66.1.176-179.2000
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin Production by Microcystis aeruginosa in a Phosphorus-Limited Chemostat

Abstract: The production of microcystins (MC) from Microcystis aeruginosa UTEX 2388 was investigated in a P-limited continuous culture. MC (MC-LR, MC-RR, and MC-YR) from lyophilized M. aeruginosa were extracted with 5% acetic acid, purified by a Sep-Pak C 18 cartridge, and then analyzed by high-performance liquid chromatography with a UV detector and Nucleosil C 18 reverse-phase column. The specific growth rate () of M. aeruginosa was within the range of 0.1 to 0.8/day and was a function of the cellular P content under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
6
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(189 citation statements)
references
References 25 publications
(21 reference statements)
12
164
6
7
Order By: Relevance
“…Many strains of Microcystis are known to produce cyanobacterial heptatoxins called microcystins (MC). Laboratory studies indicate that production of microcystin by Microcystis is affected by various environmental factors such as light, temperature, nutrients, trace elements, salinity, pH and nutrient contents in cells (Gorham 1964;Van der Westhuizen and Eloff 1985;Watanabe and Oishi 1985;Oh et al 2000;Lee et al 2000;Long et al 2001). Environmental variables are likely to influence MC concentration directly by influencing cellular microcystin production and content (Orr and Jones 1998;Long et al 2001), and indirectly by influencing cyanobacterial species and strain composition (Chorus 2001;Vézie et al 2002).…”
Section: ó Springer Science+business Media Llc 2007mentioning
confidence: 99%
“…Many strains of Microcystis are known to produce cyanobacterial heptatoxins called microcystins (MC). Laboratory studies indicate that production of microcystin by Microcystis is affected by various environmental factors such as light, temperature, nutrients, trace elements, salinity, pH and nutrient contents in cells (Gorham 1964;Van der Westhuizen and Eloff 1985;Watanabe and Oishi 1985;Oh et al 2000;Lee et al 2000;Long et al 2001). Environmental variables are likely to influence MC concentration directly by influencing cellular microcystin production and content (Orr and Jones 1998;Long et al 2001), and indirectly by influencing cyanobacterial species and strain composition (Chorus 2001;Vézie et al 2002).…”
Section: ó Springer Science+business Media Llc 2007mentioning
confidence: 99%
“…by reversetranscription QPCR al. 2007), nitrogen and phosphorus (e.g., Orr and Jones 1998;Oh et al 2000;Vézie et al 2002), micronutrients (e.g., Lukac and Aegerter 1993;Utkilen and Gjolme 1995;Lyck et al 1996), temperature (e.g., van der Westhuizen and Eloff 1985;van der Westhuizen et al 1986;Amé and Wunderlin 2005), pH (e.g., van der Westhuizen and Eloff 1983), and photon irradiance (e.g., Kaebernick et al 2000;Kardinaal et al 2007) can affect growth and toxin production. Unfortunately, in spite of this intensive research, the regulatory mechanisms behind microcystin biosynthesis and its biological function are still largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of microcystins is mediated through the inhibition of eukaryotic protein phosphatases 1A and 2A in liver cells and cause liver cancer and tumors in humans and wildlife (Carmichael 1995). Many biotic and abiotic factors such as zooplankton grazing (Jang et al 2003), phosphorus concentrations (Oh et al 2000), and nitrogen concentrations (Lee et al 2000), were shown to affect the production of microcystins by Microcystis. Recently, the influence of environmental factors on microcystins synthesis was studied in levels of transcription of mcy genes and microcystins synthetase (Mcy).…”
Section: Gene Expression Profilesmentioning
confidence: 99%